Beyond boycotts sport during the Cold War in Europe - Vonnard, Philippe; Sbetti, Nicola; Quin, Grégory 1983-; Polley, Martin 1965- (Rethinking the cold war, 2018)
"During the Cold War, sport was used as a means of diplomacy between the two blocks, allowing exchanges between East and West across the Iron Curtain. Focusing on Europe, this book offers new insights in sports history, a growing research field, which up to know offered relatively few studies on the Cold War era"...